Annual Plan 1970-71 Government of Bihar - Planning Commission (Planning Commission, 1970)
The third plan formally ended in March, 1966. For three successive years, ad hoc annual plans were adopted and from 1969-70 we entered the new Fourth Five Year Plan which however, has not yet been finally settled. The tentative financial target of the Fourth Five Year Plan is Rs.531 crores. The phasings and the sectoral distributions have been only tentatively adopted for the years 1969-70 and 1970-71. In two years ending 1970-71, about Rs.157 crores out of the proposed outlay for 5 years will have been spent representing about 30 per cent of the total target. The physical and financial targets for 1970-71 are related to those of the Fourth Five Year Plan and represent a step up over 1969-70.
Planning Department